L’Ordine dei medici di Roma e la psichiatria - Del Missier, Giovanni; Colamedici, Daniela (Il sogno della farfalla, 2010)
In the month of December 2009 a psychiatry training course for general practitioners was held at the premises of the Medical Register of Rome and Province. The organizers explain the historical institutional and theoretical-methodological motivations of this collaboration with the Medical Register.